Joint estimation of doppler frequency and DOA-DOD based on FRFT in bistatic MIMO radar system - Li LI; Tian-shuang QIU (Tongxin xuebao)
A novel method for the joint parameters estimate in the bistatic multiple-input multiple-output (MIMO) radar system was proposed.Firstly,a novel signal model to accurately estimate parameters of the et was proposed.Two Doppler parameters,initial Doppler frequency and Doppler frequency rate,were estimated by peak-searching in the fractional Fourier transform (FRFT) domain.Two sub-array models to accurately estimated the direction of departure (DOD) and direction of arrival (DOA) by employing the proposed fractional Fourier transform based MUSIC (FRFT-MUSIC) algorithm and the fractional Fourier transform ESPRIT (FRFT-ESPRIT) algorithm.Simulation results were presented to verify the effectiveness of the proposed method.